2018
DOI: 10.1371/journal.pone.0207618
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity to, oviposition and population growth impairments of Callosobruchus maculatus exposed to clove and cinnamon essential oils

Abstract: The use of plant essential oils has been shown to efficiently control insect pests of stored beans, significantly reducing the threats associated with synthetic insecticides. Here, we evaluated the potential of applications of essential oils of clove, Syzygium aromaticum L., and cinnamon, Cinnamomum zeylanicum L., to control Callosobruchus maculatus, considered as one of the most cosmopolitan pests of stored beans. Using four combinations of couples (i.e., unexposed couples, exposed females, exposed males, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 64 publications
4
18
0
Order By: Relevance
“…In a recent study, it has been shown that eugenol have a strong inhibition of acetylcholinesterase (AChE) and adenosine triphosphatases (ATPases) activities in Sitophilus oryzae, but also that the fumigant toxicities of the monoterpenes such as eugenol are higher than their contact and/ or oral toxicities (Athanassiou et al, 2014;Saad et al, 2018). Furthermore, eugenol-rich essential oils (e.g., clove essential oil) that exhibited insecticide activity similar to the activity recorded for deltamethrin (Viteri Jumbo et al, 2018) can be easily biodegraded by microorganisms (Mishra, S. & Sachan, S. 2013;Kadacol, J. & Kamanavalli, C. 2010).…”
Section: Results and Discusionmentioning
confidence: 98%
“…In a recent study, it has been shown that eugenol have a strong inhibition of acetylcholinesterase (AChE) and adenosine triphosphatases (ATPases) activities in Sitophilus oryzae, but also that the fumigant toxicities of the monoterpenes such as eugenol are higher than their contact and/ or oral toxicities (Athanassiou et al, 2014;Saad et al, 2018). Furthermore, eugenol-rich essential oils (e.g., clove essential oil) that exhibited insecticide activity similar to the activity recorded for deltamethrin (Viteri Jumbo et al, 2018) can be easily biodegraded by microorganisms (Mishra, S. & Sachan, S. 2013;Kadacol, J. & Kamanavalli, C. 2010).…”
Section: Results and Discusionmentioning
confidence: 98%
“…Significant bioactivity against pest insects has been recorded for essential oils from 1500 plant species [31]. Many studies on storage pests have shown that contact and fumigant applications of EOs increase mortality, reduce adult emergence and provoke repellent, feeding and oviposition deterrent behavioral responses [32][33][34][35][36][37][38][39][40][41][42]. Negative effects on longevity and fecundity of pests as well as life history traits of their offspring have been recorded at sublethal concentrations [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have documented that sublethal exposure to plant essential oils, or environmental changes (e.g., host changes) could impact the fitness of stored product insect pests. For example, clove and cinnamon essential oils have reported as toxic as the pyrethroid-based insecticide deltamethrin against C. maculatus and severely decreased adult emergence and egg number 16 . Host shift effects from kidney beans to cranberry beans have been studied in the bean weevil Acanthoscelides obtectus, and reproductive performance has been evaluated after exposure to clove and cinnamon essential oils.…”
Section: Resultsmentioning
confidence: 99%